Critical Review of the Book «Comprehensive Study of Russian Texts» - Nahide Kalashi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The subject of this article is about introduction and review of the book «Comprehensive Study of Russian Texts» which is compiled by Dr. Hossein Gholami and Azadeh Mozayeni from the Institute for Humanities and Cultural Studies Publication (IHCS). This book is for teaching of «Reading comprehension» and «Verbalization» for master’s students in Russian language. The passages of this book are short stories from the book «Книга для чтения». In addition to the above, in order to better understand the texts, the authors have added parts to it. There are drawbacks in terms of form, content and writing principles which cause students to have trouble reading it. So, in order to achieve pleasant results and choosing the book as a source of teaching by professors and Russian language teachers, editions and necessary information should be applied in the book in order to be used as specified targets of the authors. The book has been evaluated from the content and simulate criticism.